Utrata wartości zapasów - odpisy aktualizujące i ich wpływ na odroczony podatek dochodowy - Tatarska, Marzena (The Depreciation of Material Values of Turnover Asset - Reassessment of Turnover Assets versus the Deferred Income Tax, 2005)
In the article there are introduced the most important problems concerning the depreciation of material values of turnover assets: materials, products and commodities. According to the Accountancy Law, companies must execute reassessments which will update values of those assets. However, regulations of balance law differ from regulations of tax law in this sphere which influences the deferred income tax, therefore this issue was described thoroughly in the article. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 122-129